Combinatorics and physics: Mini-Workshop on Renormalization, December 15-16, 2006, Max Planck Institut fur Mathematik, Bonn, Germany : Conference on Combinatorics and Physics, March 19-23, 2007, Max Planck Institut fur Mathematik, Bonn, Germany - Ebrahimi-Fard, Kurusch (Contemporary mathematics, 2011)
Provides an overview of applications of combinatorics to various problems, such as applications to Hopf algebras, techniques to renormalization problems in quantum field theory, as well as combinatorial problems appearing in the context of the numerical integration of dynamical systems, in noncommutative geometry and in quantum gravity.